Determination of the Decision of the Jamaah Masjid to Pay Infaq Through the Qris Application (Case Study of the Ar-Rahman Masjid Hm. Yamin Field of Fight) - Amelia, Anika; Anggraini, Tuti; Bi Rahmani, Nur Ahmadi (Universitas Ibn Khladun Bogor, 2023)
Technology has made life more comfortable and efficient for people today. The use of QRIS and other innovative payment systems is influenced by technological developments in all areas, including the banking industry. One of the technological advancements that are in demand today is the use of QRIS as a non-financial payment mechanism. The use of QRIS has become one of the alternative payments in mosques in addition to being used for shopping payments. The Ar-Rahman Mosque is one of the mosques that uses QRIS to raise funds for infacts. This research is intended to study the variables that affect the decision of the Mosque of Ar-Rahman to inflate using QRIS.Ketua BKM Mosque and Jamaah Mosque Ar- Rahman became the main source of data in this research, which is carried out with qualitative descriptive methodology. Secondary data sources come from literature surveys. The percentage of Ar-Rahman Mosque jamaahs using QRIS is currently around 20%; however, as the BKM of the mosque continues to socialize, this number will probably continue to increase. Awareness of QRIS, the ease of using QRIS and the satisfaction of the QRIS users are factors that influence the decision of the Masjid Ar-Rahman to inflate through QRIS.